Dissecting the Quality of Arabic Textbook KMA 183 Grade 6 for Elementary School: A William Frans Mackey-Based Analysis (Al-Hasani: Journal of Islamic Studies, 2024)
This study analyzes the Arabic language textbook for 6th grade Madrasah Ibtidaiyah following the KMA 183 curriculum based on William Francis Mackey's textbook analysis theory. The focus of the analysis includes three main elements: material selection, gradation, and material presentation. This research used a qualitative approach with a content analysis method. The data obtained will be analyzed inductively using content analysis techniques, where important findings will be categorized and interpreted in relation to William Frans Mackey's theoretical framework. The research results show this textbook has fulfilled the principles proposed by Mackey in material selection by considering learning objectives, students' ability levels, duration of study time, selection of language type, and factors of learning feasibility. The gradation of the material is also presented gradually from easy to difficult according to the grouping and sorting of materials based on psychological principles. Meanwhile, the presentation of the material uses various procedures such as explanation in the mother tongue, use of objects/teaching aids, objective pictures, memory pictures, semantic pictures, and contextual procedures as recommended by Mackey. However, some weaknesses were also found, such as inconsistencies in the use of pictures and various sources of pictures.